Dynamic Testing of Mesh and Rock Bolt Support Systems - De Zoysa, Agampodi Ushan (Curtin University, 2015)
Combination of reinforcement and support systems are used to stabilize underground excavations. Results for laboratory testing under dynamic loading conditions are provided. Ground support schemes consisting of threaded bar and support elements such as weld and chain link mesh were studied. The results were compared using force- displacement and energy dissipated versus deformation. The combined systems were subjected to input velocities ranging from 5.4m/s to 7.3m/s with resulting input energy ranging from 27kJ to 57.5KJ.